DEVELOPMENT OF INTERACTIVE MULTIMEDIA ARTICULATE STORYLINE 3 BASED APPROACH (CTL) ON INTEGRATED THEMATIC LEARNING IN GRADE IV ELEMENTARY SCHOOL - Gio Afrianda; Reinita Reinita (JURNAL HANDAYANI PGSD FIP UNIMED, 2022)
Abstract: Interactive Multimedia is a presenter of content by utilizing the incorporation of content from several media in the form of text, sound, images, animation, and video. So that multimedia is presented in a computer-based program that facilitates interactive communication. With interactive multimedia can increase the interest and motivation of learning learners. The aim of this Research is to develop a Multimedia Interactive Articulate Storyline 3 Contextual Based teaching learning (CTL) approach on integrated thematic learning in Class IV elementary school that is valid and practical. This research uses the ADDDIE model with 5 stages including, Analisys (Analysis), Design (Design), Development (Development), Implementation (Implementation), and Evaluation (Evaluation). Data obtained based on validation questionnaires, teacher and student response questionnaires. The subject of this study trial was a class IV student of SDN 56 Children of Water which amounted to 23 people. Based on the material validation questionnaire obtained results of 93.75% with very valid categories, language validation obtained results of 93.75% with very valid categories, media validation obtained results of 94.59% with very valid categories. The results of the teacher practicality test in SDN 56 Anak Air obtained a result of 91.66% with a very practical category and the results of the student's preticality test obtained a result of 95.47% with a very valid category. Thus it can be concluded that articulate storyline 3 interactive multimedia has been valid and practically used to increase the interest and motivation of learning learners.Keywords: Interactive Multimedia, Articulate Storyline 3,Addie ModelAbstrak: Multimedia Interaktif adalah sebagai penyajikan konten dengan memanfaatkan penggabungan konten dari beberapa media berupa teks, suara, gambar, animasi, dan video. Sehingga multimedia tersebut tersaji dalam satu program berbasis komputer yang memudahkan komunikasi interaktif. Dengan multimedia interaktif dapat meningkatkan minat dan motivasi belajar peserta didik. Tujuan dari Penelitian ini adalah untuk mengembangkan Multimedia Interaktif Articulate Storyline 3 Berbasis Pendekatan Contextual Teaching Learning (CTL) Pada Pembelajaran Tematik Terpadu di Kelas IV SD yang valid dan praktis. Penelitian ini menggunakan model ADDDIE dengan 5 tahapan diantaranya, Analisis (Analisys), Perancangan (Design), Pengembangan (Development), Implementasi (Implementation), dan Evaluasi (Evaluation). Data yang diperoleh berdasarkan angket validasi ,angket respon guru dan siswa. Subjek ujicoba penelitian ini adalah Peserta didik kelas IV SDN 56 Anak Air yang berjumlah 23 orang. Berdasarkan dari angket validasi materi diperoleh hasil 93,75% dengan kategori sangat valid, validasi kebahasaan diperoleh hasil 93,75% dengan kategori sangat valid, validasi media diperoleh hasil 94,59% dengan kategori sangat valid. Hasil uji praktikalitas guru di SDN 56 Anak Air diperoleh hasil 91,66% dengan kategori sangat praktis dan hasil uji pratikalitas peserta didik diperoleh hasil 95,47% dengan kategori sangat valid. Dengan demikian bisa ditarik kesimpulan bahwa multimedia interaktif Articulate Storyline 3 ini telah valid dan praktis digunakan untuk meningkatkan minat dan motivasi belajar peserta didik.Kata Kunci : Multimedia Interaktif, Articulate Storyline 3,Model Addie